The Resting-State Brain Network Functional Connectivity Changes in Patients With Acute Thyrotoxic Myopathy Based on Independent Component Analysis - Yanfang Li; Min Ling; Song Huang; Xinghuan Liang; Yingfen Qin; Zuojie Luo; Jia Zhou (Frontiers in Endocrinology, 2022)
ObjectiveThe independent component analysis (ICA) was applied to explore the correlation between clinical manifestation and the functional connectivity changes of the sensorimotor network (SMN) and left frontoparietal network (LFPN) in patients with acute thyrotoxic myopathy (ATM), which was expected to provide a functional imaging basis for the exploration of the pathophysiological mechanism of ATM.Methods13 ATM patients (ATM) and 12 non-ATM patients (nATM) who met the diagnostic and inclusion criteria were enrolled. Their resting-state brain function images were obtained with resting-state functional magnetic resonance imaging (rs-fMRI). GIFT software was used for independent component analysis to obtain the brain regions with SMN and LFPN changes. The correlation between the functional connectivity of these brain regions and clinical indicators was calculated.ResultsThe SMN functional connectivity of ATM patients was increased at the posterior lobe of cerebellum, anterior lobe of cerebellum, right superior temporal gyrus, left cingulate gyrus, left precuneus, and left postcentral gyrus compared with that of nATM patients. However, it was decreased at the occipital lobe, right dorsolateral superior frontal gyrus, paracentral lobule, angular gyrus, and superior parietal gyrus (FDR correction, P<0.05). The LFPN functional connectivity of ATM patients was increased at the posterior lobe of cerebellum, middle temporal gyrus, inferior temporal gyrus, and right cingulate gyrus compared with that of nATM patients; but was decreased at frontal lobe, parahippocampal gyrus, precentral gyrus and postcentral gyrus (FDR correction, P<0.05) Correlation analysis results showed that the enhancement of SMN functional connection at right superior temporal gyrus was significantly negatively correlated with the free thyroxine level, and the decrease of SMN functional connectivity at occipital lobe was significantly positively correlated to the thyroid stimulating hormone level. The SMN and LFPN functional connectivity changes in other brain regions were not found to be significantly correlated with thyroid function parameters.ConclusionThe bulbar paralysis (such as dysphagia, dysarthria) in ATM patients may be related to the functional connectivity changes of resting-state SMN and LFPN. The fMRI is expected to be one of the objective imaging indicators for the early clinical intervention of ATM patients.